2014
DOI: 10.1148/radiol.13131837
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Cartilage Assessment in Patients with Femoroacetabular Impingement by Using T2* Mapping with Arthroscopic Verification

Abstract: The patient-specific acetabular projection with a T2* mapping overlay enabled good anatomic localization of cartilage damage defined with a T2* threshold of 28 msec and less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…To our knowledge, investigation of T2* relaxation time of acetabular cartilage with and without Gd-DTPA 2- has only been reported in our previous study and at that in a limited number of cases [10]. A systematic evaluation of the effect of Gd-DTPA 2- on T2* relaxation in cartilage is currently lacking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, investigation of T2* relaxation time of acetabular cartilage with and without Gd-DTPA 2- has only been reported in our previous study and at that in a limited number of cases [10]. A systematic evaluation of the effect of Gd-DTPA 2- on T2* relaxation in cartilage is currently lacking.…”
Section: Introductionmentioning
confidence: 98%
“…Preliminary results using T2* mapping in FAI indicate that one can distinguish normal from abnormal hip articular cartilage [6-10], while standard MR imaging lacks diagnostic accuracy for the evaluation of cartilage lesions [11]. The advantages of T2* relaxation time mapping in hip joint cartilage include wide availability on clinical scanners, shorter imaging time, independent characterization of acetabular and femoral cartilage, high image resolution, and high signal-to-noise ratio (SNR) as compared to other quantitative methods, such as T1 or T2 mapping [9].…”
Section: Introductionmentioning
confidence: 99%
“…The sacral joint surface of the sacroiliac joints is comprised of hyaline cartilage and the iliac joint surface of fibrous cartilage which represents the particularly vulnerable entheseal joint side [13]. The GRE technique has become increasingly established in musculoskeletal MRI for dedicated cartilage visualization [14,15]. However, unenhanced non-fat-saturated T1-weighted TSE sequences should also be part of the examination protocol for sacroiliac joints to rule out pathological bone marrow changes, e. g. tumor infiltrations or fractures.…”
Section: Mri Sequencementioning
confidence: 99%
“…These changes lead to shortening of the T2* times. Using these biochemical MRI techniques studies have reported (a) lower T1Gd values from dGEMRIC in the anterosuperior region in cam-type FAI, lower T1Gd values globally in pincer-type FAI, and negative correlations between alpha angle and T1Gd of the anterosuperior region (75-78), (b) higher T1ρ and T2 of both the femoral and acetabular cartilage in subjects with symptomatic FAI compared to controls, especially in the anterosuperior region (79), and (c) lower T2* in regions of acetabular cartilage damage identified during arthroscopy in symptomatic FAI subjects without radiographic OA (74) and in subjects with cartilage lesions (80)(81)(82)(83).…”
Section: Quantitative Biochemical Mrimentioning
confidence: 94%
“…In the non-contrast techniques, a loss of proteoglycans is detected as an increase in cartilage T1ρ relaxation times and a disruption of the collagen orientation with increased water content is detected as an increase in the cartilage T2 relaxation times (71)(72)(73). T2* is similar to T2 but is more sensitive to susceptibility artifacts; and hence may be able to detect the deposition of calcium hydroxyapatite and fibrocartilagenous transformation at the osteochondral junction (74). These changes lead to shortening of the T2* times.…”
Section: Quantitative Biochemical Mrimentioning
confidence: 99%